Optimization of viral RNA extraction methods for dengue virus detection in field collected Aedes albopictus / Nurul Hidayah Roslan - Roslan, Nurul Hidayah (2015)
Dengue transmission has become a global threat and a health concern in tropical and sub-tropical countries. Aedes albopictus (Skuse), has high infestation rates in both urban and suburban areas of human settlement and is endemic in many Asian countries including Malaysia. The durability of the dengue virus (DENV) has been correlated with the occurrence of transovarial transmission via its vector. The detection of transovarial DENV transmission is complex and requires high quality and concentration of viral RNA. There are many methods of extraction available in literature, some superior than others. The purpose of this study was to determine the most optimum extraction method for DENV detection and to detect transovarial transmission ofDENV using real time PCR (qRT-PCR) in field collected Ae. albopictus. A laboratory strain from USM was used to optimize the method of viral RNA extraction. Ae. Albopictus samples were collected from non-hotspot areas at Kolej Angsana, A5, UiTM Puncak Alam. The mosquitos were reared and hatched until adulthood in the laboratory. Both male and female Ae. Albopictus were selected, pooled and homogenized for RNA extraction. Modified PBS extraction with QIAamp viral RNA mini kit extraction protocol was then chosen for the sample extraction for this study. The outcome of this study has shown that the most suitable extraction method for DENV detection is by the use of modified PBS extraction method with QIAamp viral mini kit. In addition, no DENV was detected in all samples tested despite having optimized the best method for viral RNA extraction. This could be a result of the field work being collected during non-outbreak seasons, especially at non-hotspot areas. Further study is warranted to confirm these findings using a different locality.